Content And Nature Of The Service Economy (Eurasian Journal of Research, Development and Innovation, 2022)
This article provides information on the meaning and essence of the service economy, the priority of service in the economies of countries that have transitioned to a market economy, and the fact that service industries are a component of the country's economy